2020
DOI: 10.2109/jcersj2.19036
|View full text |Cite
|
Sign up to set email alerts
|

Variation of porosity and pore size during post-sintering of reaction-bonded silicon nitride doped with Y<sub>2</sub>O<sub>3</sub> and MgO additives

Abstract: Sintering of reaction-bonded silicon nitride (SRBSN) is a method of preparing Si 3 N 4 ceramics with high thermal conductivity and good mechanical properties. In the present study, by using a high purity silicon powder as the starting material and 2 mol % of Y 2 O 3 and 5 mol % of MgO as sintering additives, the phenomena including phase transformation, grain growth, densification, and pore size evolution occurred in the SRBSN process were studied. It was found that the ¡to ¢-Si 3 N 4 phase transformation coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The addition of different contents of α-Si 3 N 4 has no significant effect on the phase compositions of the porous silicon nitride with different porosity. The main phase was β-Si 3 N 4 and no α-Si 3 N 4 phase was observed, which indicated that the phase transition of α-Si 3 N 4 to β-Si 3 N 4 has been completed, and there was a small amount of glass phase Y 8 Si 4 N 4 O 14 observed [7]. The raw materials and sintering process of the intermediate layer and the superficial layers of porous laminated silicon nitride are exactly the same as the raw materials and sintering process of single layer porous silicon nitride.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of different contents of α-Si 3 N 4 has no significant effect on the phase compositions of the porous silicon nitride with different porosity. The main phase was β-Si 3 N 4 and no α-Si 3 N 4 phase was observed, which indicated that the phase transition of α-Si 3 N 4 to β-Si 3 N 4 has been completed, and there was a small amount of glass phase Y 8 Si 4 N 4 O 14 observed [7]. The raw materials and sintering process of the intermediate layer and the superficial layers of porous laminated silicon nitride are exactly the same as the raw materials and sintering process of single layer porous silicon nitride.…”
Section: Resultsmentioning
confidence: 99%
“…Because there was no addition of -Si3N4 grains for sample S0, the spontaneous nucleation rate was slow and the number of nucleation was limited, and the nucleation process of -Si3N4 grains was suppressed and grown abnormally, so there were coarse equiaxed β-Si3N4 grains for the sample S0. Because there was addition of 5wt% -Si3N4 grains for sample S5 that has more nucleation sites [4]. In addition to -Si3N4 grains nucleation and growth spontaneous, the nucleation and growth of -Si3N4 grains was directly on the crystal surface of the -Si3N4 seeds, which accelerated growth rate of -Si3N4 grains.…”
Section: Solid State Phenomena Vol315mentioning
confidence: 99%
“…Compared to diborides like ZrB 2 , oxides typically exhibit lower melting points, which leads to the formation of liquid phases or other reactions that facilitate sintering. For example, Si 3 N 4 ceramic sintering frequently utilizes Y 2 O 3 and Yb 2 O 3 as sintering additives, while also occasionally including Al 2 O 3 and MgO [18][19][20]. SiC presents challenges in sintering for densification due to its high covalent bond ratio.…”
Section: Introductionmentioning
confidence: 99%